019 Reduced activations within right mesial temporal lobe for visual episodic memory in right temporal lobe epilepsy. Issue 6 (27th May 2022) - Ramaswamy, Arjun; Sablik, Maria; Duncan, John; Buck, Sarah; Sidhu, Meneka
Abstract : Rationale: Epilepsy surgery is an effective treatment for Temporal lobe epilepsy (TLE), however memory decline occurs in up to 40% of people. Functional MRI (fMRI) can be used to determine the pre-operative functional anatomy of memory representations to guide surgical decision making and reduce the risk of memory decline. Methods: 22 healthy controls, 8 patients with right TLE (RTLE) and 10 with left TLE (LTLE), performed an overt, word and faces memory-encoding, recognition and recall fMRI paradigm with a baseline of odd-even number decisions. Statistical Parametric Mapping (SPM) was used to investigate specific brain regions associated with encoding and retrieval processes contrasted with the baseline task. One sample and two sample t-Tests were performed between controls and patient groups. Group activations are reported at p<0.001 for extratemporal and p<0.05 for mesial temporal lobe (MTL) activations. Results: A more specific memory fMRI paradigm showed distinct activations for verbal and visual memory among controls, LTLE and RTLE groups. Particularly for visual memory, the paradigm elicited greater acti- vations in controls within the right anterior MTL and right posterior MTL for face encoding and recognition respectively. These regions have been widely associated with strong encoding and retrieval of visual memory. The reduced activations in RTLE within these regions are indicative of potential visual memory decline after surgery. arjun.ramaswamy.19@ucl.ac.uk